Pengaruh Etika Bisnis Islam dan Budaya Organisasi Terhadap Peningkatan Kinerja Karyawan pada Bank Syariah Indonesia Kcp Tangerang Cimone 1 - Bilgis Kamila; Wahyu Hidayat; Zaini Ibrahim (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2024)
This study aims to analyze the influence of Islamic business ethics and organizational culture on employee performance improvement at Bank Syariah Indonesia KCP TANGERANG Cimone 1. The research method used is quantitative with data collection techniques through questionnaires. The data were analyzed using multiple linear regression. The results of the study show that Islamic business ethics and organizational culture have a positive and significant effect on improving employee performance at Bank Syariah Indonesia KCP TANGERANG Cimone 1. This means that the stronger the implementation of Islamic business ethics and organizational culture in the bank, the higher the performance of its employees.